2010
DOI: 10.18546/ijdegl.03.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Global education and cross-cultural learning: A challenge for a research-based approach to international teacher education

Abstract: This article discusses teaching competencies for global education, beginning with an outline of some of the challenges for orientation and learning which are the result of rapid globalisation. An example of a situation in a recent class is used to illustrate the kinds of professional challenges that teachers encounter, including those related to dealing with paternalism, complexity and insecurity. The consequences of these challenges for teacher education are then outlined. Finally, the discussion highlights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
0
26
0
9
Order By: Relevance
“…It can be noted that Scheunpflug (2011Scheunpflug ( , 2014 proposes similar ways for developing competence of acting and reaching for solutions through dialogues.…”
Section: Global Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…It can be noted that Scheunpflug (2011Scheunpflug ( , 2014 proposes similar ways for developing competence of acting and reaching for solutions through dialogues.…”
Section: Global Learningmentioning
confidence: 99%
“…It has also been concluded that future research in ESD, as well as the particular challenges in global learning for sustainable development (GLSD), have to focus more on support to teachers Scheunpflug, 2011Scheunpflug, , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations